Pursuing secondary vocational education programs in Chile, beyond social background - Peralta Rojas, Miski (Journal Studies of Public Policy, 2024)
This article analyzes how social background, academic performance, and future expectations influence enrollment and graduation in secondary-level technical programs in Chile. For graduation, the fields of education in the study programs are also included as predictors. This panel research uses logistic regression models by tracking a cohort of students from eighth grade through three years after the end of secondary education. The findings confirm the literature in this area, showing that social background is a strong predictor of enrollment in technical programs within the Chilean context. Academic performance has a modest but significant influence on both enrollment and graduation in technical programs, while future expectations vary between students aiming for higher-level technical programs and those aspiring to enter university programs. The findings raise questions about the choices made by students from similar social backgrounds but with different grades, expectations, and training programs (specializations).